Ongoing increase in autochthonous Salmonella Enteritidis infections, the Netherlands, June 2023 to June 2025 - Eelco Franz (Eurosurveillance, 2025)
Salmonella Enteritidis (SE) cases in humans have increased in the Netherlands, from an annual average of 281 (2017–2019) to 427 in 2023, 401 in 2024 and 209 in 2025 (January–June). This rise is paralleled by a 2.5-fold increase in SE-positive laying hen flocks. Genomic surveillance shows numerous small clusters, suggesting a diffuse transmission rather than a single point-source outbreak, which complicates outbreak investigations. Coordinated interventions in the laying hen sector are urgently needed to mitigate public health risks.